Effectiveness of Diabetic Foot Risk Factor Education on the Practice of Diabetic Foot Wound Prevention in Type 2 DM Clients - Wahyu Widagdo; Susmadi (Politeknik Kesehatan Kemenkes RI Jakarta I, 2022)
One of the common complications of diabetes mellitus is diabetic foot problems. Diabetic foot not treated properly willbe easily get sores and quickly develop into foot ulcers. Primary prevention management of diabetic foot aim to preventing foot injuries and avoid further damage and ulcers arise which can lead to amputation. The aim of this study to analyze the effectiveness of education on risk factors for diabetic foot injuries in the practice of preventing diabetic foot in clients with type 2 diabetes mellitus. The population in this study is patient who diagnosed DM in the Pasar Minggu sub-district, sample are taken according to formula of calculating number of the samples which is author use purposive sampling technique. The qualified sample is 60 respondents, consist of 30 respondents from the intervention group and 30 respondents from control group. The results showed there was a significant relationship between education and thepractice of diabetic foot prevention. Based on this research author has recommendations, which is a nurses has to educate clients to prevent complications of diabetic foot wounds, it will be reduce the amputation rate in DM clients by involving the family.